Pendampingan Penyusunan Laporan Keuangan Sederhana UMKM - Rahmadhani, Sari; Salim, Noor; Rozak, Hasan Abdul; Dili, Agustinus Jaha; Laila, Nazil Rizki (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The development of Micro, Small, and Medium Enterprises (MSMEs) is a key driver of regional economic growth, contributing to job creation and improved living standards for the people. However, MSMEs in many regions, including Tunggulsari Village, still face serious obstacles in financial management, especially in recording and preparing simple and structured financial statements. This problem is caused by low financial literacy and a lack of continuous, intensive assistance from the government. Community service involving technical training and ongoing mentoring has proven effective in enhancing the financial management capabilities of MSMEs. Through adaptive mentoring programs and the use of simple technology, MSMEs are able to build a good, accurate, and regular recording culture that supports easier business decision-making and access to financing. This study shows that the implementation of the program in Tunggulsari Village has succeeded in improving MSMEs' understanding of financial management and record-keeping, although there is still a need for improvement in the understanding of production costs and the cost of products.